Correlative Assessment of Hemodynamic Parameters Obtained with T2*-weighted Perfusion MR Imaging and SPECT in Symptomatic Carotid Artery Occlusion - Hyoung Kim, Jae; Joo Lee, Sun; Shin, Taemin; Hun Kang, Kyeong; Youb Choi, Pil; Hee Kim, Jung; Chul Gong, Jae; Choi, Nack-Cheon; Hoon Lim, Byeong (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Perfusion MR imaging and single-photon emission CT (SPECT) are commonly used to evaluate hemodynamic status in patients with symptomatic occlusive cerebrovascular disease. These techniques rely on different underlying physiological mechanisms, and the data may not correspond. We studied the relationship between hemodynamic parameters obtained with these two methods.METHODS: We performed perfusion MR imaging and SPECT in 10 patients with symptomatic unilateral internal carotid artery occlusion. Relative cerebral blood volume (rCBV) and uncorrected mean transit time (uMTT) were obtained with dynamic contrast-enhanced T2*-weighted MR imaging. Relative cerebral blood flow (rCBF) and vascular reserve capacity were measured with 99mTc-HMPAO SPECT; vascular reserve capacity was calculated by the difference in CBF before and after acetazolamide challenge. Ratios of these hemodynamic parameters between the affected and contralateral vascular territories were calculated and compared.RESULTS: Normal-to-increased CBV, prolonged uMTT, decreased CBF, and normal-to-diminished vascular reserve capacity were observed in the affected vascular territories. Reduction of vascular reserve capacity corresponded well with uMTT but not with CBF and CBV. CBF, CBV, and uMTT did not correspond to one another.CONCLUSION: uMTT is more sensitive than the other parameters in estimating vascular reserve capacity. The relationship between parameters obtained with perfusion MR imaging and SPECT should be considered in assessing the hemodynamic status of patients with symptomatic occlusive cerebrovascular disease.